PENGARUH TINGKAT PENGETAHUAN TERHADAP PELAKSANAAN PEMAKAIAN ALAT PELINDUNG DIRI SEBAGAI UPAYA PENCAPAIAN ZERO ACCIDENT DI PT. X - Seviana Rinawati; Nilan Nur Widowati; Eka Rosanti (Journal of Industrial Hygiene and Occupational Health, 2016)
This study aim to determine the effect of knowledge toward Personal Protection Equipment usage to create the discipline of the labor force as an attempt zero accident achievement on the Spinning sector. This study applied observational analytical research using cross-sectional approach. Sampling technique using purposive sampling. As the object of study sample is 55 people. Data taken using questionnaires and observation sheets to know the characteristics of respondents, measuring knowledge, and personal protection equipment usage. Processing techniques and data analysis performed with Chi Square statistical test. The results by Chi Square test is known that the sig. as same as 0,009, or less than 0.05. Most respondents have a high knowledge level, while the implementation of PPE usage is mostly labor discipline. For conclusion of study, there is influence of knowledge toward Personal Protection Equipment (PPE) usage in the labor force spinning sector at  PT. X with value 6,839.  For further research to the study of other factors that influence the performance of the PPE usage in the workplace. Keywords: Knowledge; PPE usage; Zero Accident